2014
DOI: 10.1007/s00232-014-9724-2
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Activates Volume-Sensitive Like Chloride Channels Via Purinergic Receptor Pathways in Nasopharyngeal Carcinoma Cells

Abstract: Cisplatin-based concomitant chemoradiotherapy is considered as the standard treatment for locally advanced nasopharyngeal carcinoma patients. However, the curative efficacy of cisplatin-based chemotherapy is limited because of the occurrence of cisplatin resistance. Some researches indicate that activating the volume-sensitive Cl(-) channel might be a new strategy for the reduction of cisplatin resistance. However, little is known about the activation pathway of the Cl(-) channels activated by cisplatin. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The VSOR currents were found to be voltagedependently inhibited by a tyrosine kinase inhibitor, genistein (Bryan-Sisneros et al, 2000;Shuba et al, 2000;, but not by its inactive analog daidzein . An antiestrogen, tamoxifen, which is a known inhibitor of P-glycoprotein, was found to voltage-independently inhibit VSOR activity in a number of nonexcitable cells (Zhang et al, 1994;Tominaga et al, 1995b;Meyer and Korbmacher, 1996;Wondergem et al, 2001;Chen et al, 2002;Hélix et al, 2003;Yang et al, 2015) and colonic smooth muscle cells (Dick et al, 1999). In contrast, tamoxifen was ineffective in inhibiting VSOR in neuronal (Leaney et al, 1997;Inoue et al, 2005Zhang et al, 2011) and muscular (Voets et al, 1997) cells as well as in some epithelial cells (Winpenny et al, 1996;Mitchell et al, 1997b) and neutrophils (Ahluwalia, 2008b).…”
Section: B Volume-sensitive Outwardly Rectifying Anion Channel Blockersmentioning
confidence: 99%
“…The VSOR currents were found to be voltagedependently inhibited by a tyrosine kinase inhibitor, genistein (Bryan-Sisneros et al, 2000;Shuba et al, 2000;, but not by its inactive analog daidzein . An antiestrogen, tamoxifen, which is a known inhibitor of P-glycoprotein, was found to voltage-independently inhibit VSOR activity in a number of nonexcitable cells (Zhang et al, 1994;Tominaga et al, 1995b;Meyer and Korbmacher, 1996;Wondergem et al, 2001;Chen et al, 2002;Hélix et al, 2003;Yang et al, 2015) and colonic smooth muscle cells (Dick et al, 1999). In contrast, tamoxifen was ineffective in inhibiting VSOR in neuronal (Leaney et al, 1997;Inoue et al, 2005Zhang et al, 2011) and muscular (Voets et al, 1997) cells as well as in some epithelial cells (Winpenny et al, 1996;Mitchell et al, 1997b) and neutrophils (Ahluwalia, 2008b).…”
Section: B Volume-sensitive Outwardly Rectifying Anion Channel Blockersmentioning
confidence: 99%
“…Furthermore, we found that 18 h Cisplatin exposure resulted in a 2- to 2.5-fold increase in the LRRC8A protein content in A2780WT, whereas its expression in A2780CisR was unaffected ( 44 ). Recent studies performed by Yang and coworkers ( 55 ) have indicated that Cisplatin activates a Cl − current in nasopharyngeal CNE-2Z carcinoma cells, which exhibits properties similar to VRAC (outward rectification, ATP dependence, selectivity sequence of I − > Br − > Cl − > gluconate), and which could be inhibited by the anion channel blocker tamoxifen and extracellular ATP. Studies by Planells-Cases and coworkers ( 36 ) indicate that Cisplatin induced taurine release and the cytotoxic effects of the chemotherapeutic drugs Staurosporine, Cisplatin and Carboplatin are abolished in LRRC8A and LRRC8D knockout HEK cells ( 36 ).…”
mentioning
confidence: 99%
“…For example, SITS/DIDS and glibenclamide were found to exhibit voltage-dependent blocking action on VSOR/VRAC currents originally by Kubo & Okada [ 65 ] and Liu et al [ 96 ], respectively. Suramin 6− was also shown to be an open-channel blocker of VSOR/VRAC [ 64 , 72 , 90 , 108 111 ]. The open-channel blocking actions are very interesting from the viewpoint of the pore size estimation.…”
Section: Phenotypical Properties Of Vsor/vracmentioning
confidence: 99%